(untitled) (International Journal of Biology and Chemistry, 2015)
One of the most important problems of probiotics production is the development of non-waste technologies, in particular, usage of microbial cultures fugate. In conventional technology, it must be disposed of after the intensive heat treatment in drains. The fugate does not contain bacteria, but rather products of their metabolism and biosynthesis, which may have therapeutic, preventive and growth-stimulating effects. The above mentioned fact shows the relevance of the development of non-waste technology of feed probiotics of the genus Bacillus and their metabolites. In al-Farabi Kazakh National University, at Biotechnology Department of Faculty of Biology and Biotechnology were obtained experimental samples of probiotic feed additives – SUBACIL. SUBACIL-1 is lyophilized biomass of Bacillus subtilis P-2 containing 9х1012 spores in 1g. SUBACIL-2 is a combined feed probiotic comprising metabolites of B.subtilis P-2 immobilized on sunflower meal with addition of soya flour hydrolyzate. In this study was investigated the impact of feed additives SUBACIL-1 and SUBACIL-2 for growing of broiler chickens, in accordance with the following factors: changes of body weight, average daily gain and safety of the birds. The addition SUBACIL-1 of feeding for broilers increases the productivity of poultry meat by 11%, SUBACIL-2 – 9%. The use of new additives during the growing period is accompanied by the increase in average daily gain. When using of SUBACIL-1 daily gain is by 9.7% more than that of control group and 2.4% while using of SUBACIL-2. The introduction of these additives allows gaining 90% (SUBACIL-1) and 85% (SUBACIL-2) preservation of livestock. The greatest efficiency index was 214.94.